VARIASI KOMPOSISI BAHAN BAKU TERHADAP MUTU ORGANOLEPTIK MIE TEPUNG PISANG - Dewi Siti Rahayu; Siska Apriyani; Ahmad Zueni (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2014)
Banana flour noodles are processed products of banana length , where in the processing process is fairly easy . Banana flour noodles in the treatment process through several stages of the process of sorting , washing , mixing , molding until boiling . Of these processes are one of the processes that determine the quality of banana flour noodles can be determined from the organoleptic properties of banana flour noodles . The purpose of this study was to determine the effect of the addition of banana flour on the organoleptic quality of banana flour noodles.The study was conducted with three treatments , namely the first treatment process carried out by the addition of 100 grams of banana flour , the second treatment is done by adding 200 grams of banana flour and treatments to three performed with the addition of 300 grams of banana flour . Analysis is conducted organoleptic analysis . The conclusion of this study found that in terms of the parameters of color , flavor , and texture of banana flour noodles that is most favored by the addition of 200 grams of banana flour .Keywords : Noodles , Banana flour , Organoleptic properties